The use of nanocrystalline and two other forms of calcium sulfate in the treatment of infrabony defects: A clinical and radiographic study - Nymphea Pandit; Aditi Sharma; Ashish Jain; Deepika Bali; Rajvir Malik; Shalini Gugnani (Wolters Kluwer Medknow Publications, 2015)
Background: Calcium sulphate(CS) is one of the oldest alloplastic graft materials used because of its biocompatibility, handling characteristics, porosity, different rates of dissolution, chemico-physical resemblance to bone mineral, ability to induce release of growth factors and potentially unlimited supply at a modest cost. Aim of the study was to evaluate the efficacy of 3 forms of calcium sulphate i.e. Nanogen (nCS)(+), BoneGen(+) and Dentogen(+) in treatment of infrabony defects and to compare their efficacy as bone grafting substitutes. Materials and Methods: A prospective randomized, double blind controlled study was conducted on 45 sites from 16 subjects having Moderate to Advanced Periodontitis who were divided into 3 groups i.e. Group I (Nanogen), Group II (Dentogen) and Group III (BoneGen) clinical along with radiographic measurements were taken at baseline, 6 and 12 months postoperatively. Results: There was no significant inter-group difference in mean clinical attachment level (CAL) values at different time intervals whereas Intra-group changes in CAL at 6 and 12 months as compared to baseline were significant statistically. In Group I, changes in CAL between 6 and 12 months were found to be statistically significant in comparison with Group II and III. Conclusion: Both Nanogen and BoneGen TR can be considered valuable options in the treatment of infra-bony periodontal defects. The faster degradation of Dentogen may negatively affect its bone regeneration potential.